Secretome Analysis Performed During in vitro Cardiac Differentiation: Discovering the Cardiac Microenvironment - Robert, Anny Waloski; Pereira, Isabela Tiemy; Dallagiovanna, Bruno; Stimamiglio, Marco Augusto (Frontiers in Cell and Developmental Biology, 2020)
Human pluripotent stem cells are an important tool for the study of developmental processes, such as cardiomyogenic differentiation. Despite the advances made in this field, the molecular and cellular signals involved in the commitment of embryonic stem cells to the cardiac phenotype are still under investigation. Therefore, this study focuses on identifying the extracellular signals involved in in vitro cardiac differentiation of human embryonic stem cells. Using a three-dimensional cardiomyogenic differentiation protocol, the conditioned medium and the extracellular matrix (ECM) of embryoid body cultures were collected and characterized at four specific time points. Mass spectrometry (MS) and antibody array analysis of the secretome identified a number of secreted proteins related to signaling pathways, such as Wnt and TGFβ, as well as many ECM proteins. When comparing the proteins identified at selected time points, our data pointed out protein interactions and biological process related to cardiac differentiation. Interestingly, the great changes in secretome profile occurred during the cardiac progenitor specification. The secretome results were also compared with our previous RNAseq data, indicating that the secreted proteins undergo some level of gene regulation. During cardiac commitment it was observed an increase in complexity of the ECM, and some proteins as IGFBP7, FN1, HSPG2, as well as other members of the basal lamina could be highlighted. Thus, these findings contribute valuable information about essential microenvironmental signals working on cardiomyogenic differentiation that may be used in future strategies for cardiac differentiation, cardiomyocyte maturation, and in advances for future acellular therapies.